Towards a social and food justice for agricultural day laborers with internal migration in Mexico - Villalobos-Pérez, Ariadna Guadalupe; López, Maria de Lourdes Flores; Théodore, Florence L; Villanueva-Borbolla, María Ángeles; Saldaña, Kim Sánchez (Cadernos de saúde pública, 2025)
This study aimed to characterize the food environment of internal agricultural migrant workers in Mexico and to build scenarios in prospective terms to formulate alternatives that guide food and agriculture policies based on a social justice approach. Qualitative methods were used, including semi-structured interviews with women who are laborers and specialists in the subject, observation in chili cultivation fields in Guanajuato, image capture, as well as food foresight workshops. The data were analyzed via content analysis. Internal agricultural migrant workers face systematic disadvantages throughout migration, inscribed in a context of high vulnerability and discrimination. They live in a precarious situation, both in terms of work and access to adequate food, immersed in an unhealthy food environment, surrounded by deserts and food swamps. A plausible scenario in which they can migrate under fair conditions and with guarantees of their labor and food rights. Internal agricultural migrant workers' six dimensions of social justice to achieve well-being are not covered, reflected in a food environment that promotes injustices, inequality, and food vulnerability. The acute need for public policies aimed at improving working, living, and food conditions in rural areas by promoting local economies, and seeking to make migration an option and not an obligation, is reinforced. Implementing such policies would not only improve their lives but also promote a fairer food model for the Mexican countryside, based on food sovereignty.